Az ukrán nyelv Kárpátalján - Csernicskó István; Черничко Степан; Csernicsko Istvan (Teleki László Alapítvány Közép-Európa Intézet, 1998)
Az ukrán nyelv oktatását 1990-ben minden ukrajnai, így a kárpátaljai magyar iskolákban is bevezették. Az ukrán nyelv oktatásához a kárpátaljai magyar iskolákban azonban nincsenek meg az alapvető feltételek. 1. Nincsenek a magyar iskolák számára készült ukrán nyelvtankönyvek. 2. Az iskolák számára nem készültek magyar-ukrán és ukrán-magyar szótárak. 3. Hiányoznak a szaktanárok. általában az orosztanárokra hárul az ukrán nyelv oktatása, esetleg azokra a pedagógusokra, akik valamennyire beszélik a nyelvet. 4. Végleges tanterv sincs a nemzetiségi iskolák számára. 5. Kidolgozatlanok az ukrán nyelv oktatásának módszertani alapelvei is, hisz mind ez idáig az ukrán nem volt tantárgy a kárpátaljai magyar iskolákban. Ennek ellenére az Ukrajna elnöke által jóváhagyott Nemzeti Alaptantervben az áll, hogy minden középiskolai végzősnek megfelelő szinten tudnia kell az ukránt mint államnyelvet.

Abstract. Following the 1989 Ukrainian language law, the teaching of the state language (Ukrainian) became mandatory in public schools in 1990. Prior to 1990, when Ukraine was part of the USSR, high school students in Ukraine did not have to take a school leaving exam in Ukrainian if they attended a Russian-language school. In 1989-90, Ukrainian was mandatorily taught to only 45 % of all primary and secondary school pupils. At the same time nationality proportion of Ukraine was: 72 % Ukrainian, 22 % Russian. The introduction of the mandatory teaching of Ukrainian in the schools of indigenous Hungarians (c.155 000) Subcarpathia generated social and pedagogical conflicts. There are no schoolbooks and bilingual dictionaries for the teaching of Ukranian to Hungarians. There are few trained teachers of Ukrainian and there is no accepted curriculum for teaching the state language. The state requires all pupils to know the state language but does not provide adequate educational opportunities. Consequently a major conflict occurs when Hungarian students take entrance exams in the State University of Uzhorod.
The Ukrainian in Subcarpathia
http://real.mtak.hu/24435/1/Regio_kisebbseg_politika_tarsadalom_1998._9._evf._1._sz._u.pdf
Keywords: Kárpátalja; ukrán nyelv; nyelvhasználat; nyelvoktatás